Sustainable housing design to improve the quality of life of the inhabitants of zone “Z” Ate Huaycan 2023 - Bazán Mancco, Yajhayra Angielina (2024)
The demographic increase in Peru has led to the construction of numerous homes built with traditional materials, inaccessible to those with limited resources, especially affecting a large number of residents concentrated in the "Z" zone of Ate - Huaycán. These inhabitants find themselves in unhealthy and inaccessible housing, resulting in uninhabitable construction with a shortage of conventional and nonconventional materials. Furthermore, these homes lack basic services due to the economic limitations of the inhabitants. To address this problem, a survey was carried out that evaluated various aspects related to sustainable housing and quality of life in 20 homeowner families in the "Z" zone of Ate - Huaycán. This survey was validated by an advisor and experts in the field, and one question was applied per family. As part of the solution, a sustainable housing prototype was designed for the residents of the area, using AutoCAD software for 2D modeling. This design has dimensions of 19 x 9.5 m2 and an optimal height to allow the entry of natural light and adequate ventilation. The results of the surveys indicate that sustainable homes represent a favorable alternative to improve housing conditions, since they offer greater comfort and contribute to reestablishing a more adequate living environment. In addition, the SketchUp version 2021 program was used to support the design and creation of visual representations of the home.